2020
DOI: 10.3390/jcm9061922
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anti-Viral Treatment for Chronic Hepatitis B

Abstract: Adherence to treatment of chronic Hepatitis B Virus (HBV) is an important issue and can affect the complication rate. Nucleos(t)ide analogue as oral treatments are used for patients with necro-inflammatory activity and high viral load, with the goal of decline the complication rate such cirrhosis and hepatic cancer. We aimed to investigate the adherence to chronic HBV treatment. Chronic HBV patients with dispensing medication rates (DMR) of at least 80% were defined as high adherence group (HAG) and those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Long-term NUC treatment can present challenges, including poor adherence, economic burdens and psychological stressors. 27 A large nationwide Japanese study revealed that a significant number of CHB patients starting antiviral therapy expressed concerns about medication costs. 28 Moreover, some patients reported that the need for treatment made them perceive themselves as sicker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term NUC treatment can present challenges, including poor adherence, economic burdens and psychological stressors. 27 A large nationwide Japanese study revealed that a significant number of CHB patients starting antiviral therapy expressed concerns about medication costs. 28 Moreover, some patients reported that the need for treatment made them perceive themselves as sicker.…”
Section: Discussionmentioning
confidence: 99%
“…While treatment can have positive effects, such as increased confidence, especially in patients with undetectable viral loads who are less likely to transmit the virus, it is important to acknowledge that negative aspects exist as well. Long‐term NUC treatment can present challenges, including poor adherence, economic burdens and psychological stressors 27 . A large nationwide Japanese study revealed that a significant number of CHB patients starting antiviral therapy expressed concerns about medication costs 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 529 patients with HBV reactivation, 70.9% of them were triggered by cessation of antiviral treatment. Although both guidelines of APASL, EASL, and AASLD have put forward elaborate recommendations on NUCs treatment and withdrawal, it is still common in clinical practice that patients have poor adherence and stop NUCs treatment under various reasons, with a reported treatment adherence about 46.4%–74.6% ( Ford et al, 2018 ; Abu-Freha et al, 2020 ), which may results in virological breakthrough and increasement of mortality ( Abu-Freha et al, 2020 ). Taken together, it suggests that more attention should be paid on the adherence of antiviral treatment in CHB patients to avoid HBV reactivation and its related critical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…adherence and stop NUCs treatment under various reasons, with a reported treatment adherence about 46.4%-74.6% (Ford et al, 2018;Abu-Freha et al, 2020), which may results in virological breakthrough and increasement of mortality (Abu-Freha et al, 2020). Taken together, it suggests that more attention should be paid on the adherence of antiviral treatment in CHB patients to avoid HBV reactivation and its related critical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it might be relevant to know the rate of adherence to treatment of other asymptomatic viral infections in the same population. For example, in a study we conducted, there was no significant difference between the AB and Jewish people living in the Negev regarding adherence to chronic hepatitis B treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%